Measurement and statistical analysis toward reproducibility validation of AZ4562 cylindrical microlenses obtained by reflow - Maciel, Marino Jesus Correia (2014)
This paper presents the statistical analysis applied into the shape of microlenses (MLs) for validating the high-reproducibility feature of their fabrication process. The MLs were fabricated with the AZ4562 photoresist, using photolithography and thermal reflow processes. Two types of MLs arrays were produced for statistical analysis purposes: the first with a cross-sectional diameter of 24 μm and the second with a cross-sectional diameter of 30 μm, and both with 5 μm spacing between MLs. In the case of 24 μm diameter arrays, the measurements showed a mean difference in diameter of 2.78 μm with a standard deviation (SD) of 0.22 μm (e.g., 2.78 ± 0.22 μm of SD) before the reflow, and 2.34 ± 0.35 μm of SD after the reflow. For the same arrays, the mean difference in height obtained was, comparatively to the 5.06 μm expected, 0.76 ± 0.10 μm of SD before the reflow and 1.91 ± 0.15 μm of SD after the reflow, respectively. A mean difference in diameter of 2.64 ± 0.41 μm of SD before the reflow, and 1.87 ± 0.34 μm of SD after the reflow was obtained for 30 μm diameter MLs arrays. For these MLs, a mean difference in height of 0.71 ± 0.12 μm of SD before the reflow and 2.24 ± 0.24 μm of SD after the thermal reflow was obtained, in comparison to the 5.06 μm of height expected to obtain. These results validate the requirement for reproducibility and opens good perspectives for applying this fabrication process on high-volume production of MLs arrays.